Determination of atomistic deformation of tricalcium silicate paste with high‐volume fly ash. Issue 12 (13th August 2020) - Jee, Hyeonseok; Im, Sumin; Kanematsu, Manabu; Suzuki, Hiroshi; Morooka, Satoshi; Taku, Koyama; Machida, Akihiko; Bae, Sungchul
Abstract: We examined the effect of incorporating high‐volume fly ash on the atomic arrangement and interatomic deformation behavior of calcium silicate hydrates in tricalcium silicate paste upon exposure to external forces. The interatomic structural changes and strains under compressive load were assessed using synchrotron in situ high‐energy X‐ray scattering‐based atomic pair distribution function analysis. Three different types of strains, which were (a) macroscopic strains from gauges on the surfaces of specimen, (b) strains in a reciprocal space (Bragg peak shift), and (c) strains in real space (PDF peak shift), were compared to each other. All monitored and calculated strains for tricalcium silicate‐fly ash (50 wt% fly ash) paste were compared with the counterparts of the pure tricalcium silicate paste. Pair distribution function analysis in the range of r < 10 Å indicated that the atomic arrangement of tricalcium silicate‐fly ash was similar to that of synthetic calcium silicate hydrates followed by that of pure tricalcium silicate paste. Moreover, the pair distribution function refinement results revealed that the calcium silicate hydrate structure in tricalcium silicate‐fly ash paste was similar to tobermorite 11 Å, unlike that in pure tricalcium silicate paste. The interatomic strain of tricalcium silicate‐fly ash in the real space ( r < 20 Å) was smaller than that of tricalcium silicate under compression, which suggested that the incompressibility of calcium silicate hydrates at atomistic scale was enhanced by the incorporation of fly ash into it. This was likely to be caused by the increased silicate polymerization of calcium silicate hydrates, which was attributed to the increase in the amount of silicate in their structure via the addition of fly ash.